Physicochemical Characterization, Cytotoxic Activity, and Caspase-9 Expression of Nanogold-Parijoto (Medinilla Speciosa Reinw .Ex, Bl ) in Hela Cell Lines - Artanti, Anif Nur; Rohmani, Sholichah; Prihapsara, Fea; Utami, Diyah Tri; Amaris Susanto, Nindita Clourisa; Zulphadly, M.Fiqri; Meitasari, Annisa Diyan; Darojati, Ulfa Afrinurfadhilah; Untari, Meta Kartika; Sasongko, Heru; Ermawati, Dian Eka (Indonesian Society for Cancer Chemoprevention, 2024)
Parijoto (Medinilla speciosa, Reinw. ex. Bl.), a tropical plant native to Southeast Asia, contains flavonoids, tannins, and saponins, which have the potential as an anticancer. Gold nanoparticle-based drug formulations are applied to increase the anticancer effectiveness of herbal medicines. The compounds in the stalk of parijoto have the potential to be bioreductor in the biosynthesis of gold nanoparticles. This study aims to determine the physicochemical characterization, cytotoxic activity, and expression of protein caspase-9 after treatment with nanogold parijoto (AuNPs-PR) on HeLa cell. The nanogold biosynthesis process was done by reacting 1 mM HAuCl4 with parijoto aqueous extract (EP). Physicochemical characterization measure of particle size, Polydisperse Index (PdI), and zeta potential of AuNPs-PR was carried out using a particle size analyzer. The cytotoxic effect and viability cell of AuNPs- PR were carried out using the MTT assay. The expression of caspase-9 was observed by immunocytochemistry assay. Physicochemical characterization of AuNPs-PR shows that the particle size value is 160.8 nm with PdI and zeta potential values of 0.430 and -4.56 mV respectively. In the MTT assay, both AuNPs-PR and EP demonstrated a reduction in the viability of Hela cells after 24 h in a dose-dependent manner, yielding IC50 values of 3.28 μg/mL and 19.22 μg/mL, respectively. AuNPs-PR and EP showed low cytotoxic activity against Vero normal cells, with IC50 values of over 500 μM. Further, the immunocytochemistry assay indicated that there was upregulation of caspase-9 by their expression. These results indicate that AuNPs-PR could effectively induce apoptosis in HeLa cells by upregulating caspase-9.Keywords: caspase-9, HeLa cells, MTT, nanogold, parijoto.